2023
DOI: 10.1186/s40537-023-00748-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of machine learning methods for ozone pollution prediction

Abstract: Precise and efficient ozone ($$\hbox {O}_{3}$$ O 3 ) concentration prediction is crucial for weather monitoring and environmental policymaking due to the harmful effects of high $$\hbox {O}_{3}$$ O 3 pollution levels on human health and ecosystems. However, the complexity of $$\hbox {O}_{3}$$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…It is a curve drawn in 𝑇𝑃 and 𝐹𝑃 coordinates according to different decision valves. [35] 𝐴𝑈𝐶is the area around the coordinate axis under the ROC curve, ROC curve is generally located on the 𝑦 = 𝑥 line, therefore 𝐴𝑈𝐶 value is generally between 0.5 and 1, the closer to 1 means the better detection method.…”
Section: Evaluating Indicatormentioning
confidence: 99%
“…It is a curve drawn in 𝑇𝑃 and 𝐹𝑃 coordinates according to different decision valves. [35] 𝐴𝑈𝐶is the area around the coordinate axis under the ROC curve, ROC curve is generally located on the 𝑦 = 𝑥 line, therefore 𝐴𝑈𝐶 value is generally between 0.5 and 1, the closer to 1 means the better detection method.…”
Section: Evaluating Indicatormentioning
confidence: 99%
“…To improve the performance of the RFR and XGBoost models, a distribution lag was applied to the derived case fatality rate variable. Distribution lags play important roles in explaining the short-run dynamic and long-run cumulative effects of features on a response variable [47], [48]. Time lag variables were created for the previous day's, week's, and month's case fatality rate using the shift() method from the Pandas Library in Python.…”
Section: ) Random Forest Regressor With Distribution Lag and Extreme ...mentioning
confidence: 99%
“…Deep learning often requires a large amount of training data to improve the accuracy and robustness of the model, and a small amount of data suffers from many problems, such as difficulty in convergence and overfitting. Therefore, machine learning is the main method used in prediction studies and performs well with small samples [50,51]. Kawamura et al [35,44] found that the machine learning model showed higher accuracy than the traditional linear model (e.g., multiple linear stepwise regression and partial least squares) when predicting soil parameters (e.g., N and P) using Vis-NIR.…”
Section: Introductionmentioning
confidence: 99%